2018
DOI: 10.1016/j.rboe.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin expression and histomorphometric evaluation in Wistar rats subjected to neural mobilization after compression of the median nerve

Abstract: ObjectiveTo evaluate the neurotrophin mRNA expression and axon count in the median nerve of Wistar rats submitted to neural mobilization (NM) after nerve compression.MethodsEighteen animals were randomly divided into G1 (nerve compression only), G2 (NM for 1 min), and G3 (NM for 3 min). For NM, the animals were anesthetized and the right scapula received the mobilization, adapted as indicated for humans, on alternate days, from the third to the 13th postoperative (PO) day, totaling six days of therapy. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…El resultado de nuestra revisión no concuerda con el metaanálisis realizado por Basson que obtiene un TE mucho más alto (25), Nuestros resultados sobre pruebas de evocación contradicen la investigación realizada sobre el STC que señala que las técnicas de movilización neural producen una disminución de la sensibilidad nerviosa (26) disminuyendo la liberación de citoquinas (27) y aumentando la concentración en sangre de sustancias analgésicas. Apoyando nuestros resultados existen estudios de laboratorio que señalan que la aplicación de la movilización neural no modifica la sensación nociceptiva tras la compresión del nervio mediano (28) y que la técnica no altera el proceso de regeneración nerviosa (29). Nuestro resultado coincide con otra revisión (25) que indica la falta de efecto de esta técnica sobre el test de Phalen.…”
Section: Resultados Y Discusiónunclassified
“…El resultado de nuestra revisión no concuerda con el metaanálisis realizado por Basson que obtiene un TE mucho más alto (25), Nuestros resultados sobre pruebas de evocación contradicen la investigación realizada sobre el STC que señala que las técnicas de movilización neural producen una disminución de la sensibilidad nerviosa (26) disminuyendo la liberación de citoquinas (27) y aumentando la concentración en sangre de sustancias analgésicas. Apoyando nuestros resultados existen estudios de laboratorio que señalan que la aplicación de la movilización neural no modifica la sensación nociceptiva tras la compresión del nervio mediano (28) y que la técnica no altera el proceso de regeneración nerviosa (29). Nuestro resultado coincide con otra revisión (25) que indica la falta de efecto de esta técnica sobre el test de Phalen.…”
Section: Resultados Y Discusiónunclassified
“…Therefore, in the present research, due to obesity induction being performed with the supply of a hyperlipidic diet, the validation of the reference gene is of crucial importance in the correct interpretation of the final data. Development, v. 9, n. 11, e1599119702, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9702 In a recent systematic review, 1700 papers were evaluated and found that most had inadequate standardization procedures or did not possess them (Bustin et al, 2013) and some recent studies actually do not mention validation of genes (Li et al, 2014;Silva et al, 2015;and Marcioli et al, 2018). One of the possible causes of this fact is the lack of information about the importance of the validation of the reference genes in each tissue to be studied, not only in the studied species.…”
Section: Discussionmentioning
confidence: 99%
“…The 13 animal studies compared nerve mobilisation, 22,25,49,[75][76][77] spinal mobilisation, 65 spinal manipulation, 24,84,85 and knee 68 and ankle 50,72 mobilisation with no intervention or sham in male Wistar rats (n 5 98), 22,24,25,49,50,68,[75][76][77] Sprague-Dawley rats (n 5 26), 84,85 Swiss mice (n 5 16), 72 and female Wistar rats (n 5 6). 65 Spinal manipulation and mobilisation was mimicked using an activator-assisted spinal device 24,84,85 or computer-controlled feedback motor.…”
Section: Description Of Study Characteristicsmentioning
confidence: 99%
“…65 Spinal manipulation and mobilisation was mimicked using an activator-assisted spinal device 24,84,85 or computer-controlled feedback motor. 65 Several models for neuropathic pain were used, such as chronic constriction injury (CCI) to the sciatic nerve, 22,25,[75][76][77] crush injury to the sciatic 50 or median 47,48,49 nerve, compression-decompression of the DRG, 85 and injection of inflammatory mediators within the intervertebral foramen. 84 Ankle joint inflammation, 68,69,83 chronic postischemia hind paw pain, 72 knee joint immobilisation, 24 and nerve growth factor (NGF)-induced back pain 65 were also used.…”
Section: Description Of Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation